Tensile strength comparison between peroneus longus and hamstring tendons: A biomechanical study. (2017) - Rudy,; Mustamsir, Edi; Phatama, Krisna Yuarno
Abstract: Introduction: Soft tissue injuries, particularly ligaments and tendons, are the most common injuries in sports, account for more than 50% of all injuries and often require orthopedic surgery. According to data in the general population, the incidence rate of anterior cruciate ligament (ACL) injury was 1:3500. The treatment option of ACL injury cases include physical exercise and reconstruction surgery. Graft options for the ACL reconstruction include:autograft and allograft. One of the most popular autograft is hamstring. The use of hamstrings in ACL reconstruction still arguing among the expert. The choice of autograft that can be chosen as a new alternative is the peroneus longus tendon. Currently, there is very few biomechanical study on peroneus longus strength as an alternative choice of autograft in ACL reconstruction. The study to determine the tensile strength of the peroneus longus tendon was conducted by the researcher as a preliminary study that could bring new perspective for future studies. Materials and methods: This is an experimental research. Six human cadaveric specimens as research material. Each cadaver was treated by taking hamstring and peroneus from both lower limbs. The hamstring and peroneal tendons were then measured by applying the Hydraulic Servo Pulser tensile test apparatus. Data on tensile strength comparison between peroneal tendon and hamstring were analyzed by descriptive and inferential statistics. Result: From the measurement results, it is known that hamstring has lower average tensile strength value compared to peroneus without significant difference (p > 0.05). Conclusion: The tensile strength of the peroneus longus tendon, which is similar to that of hamstring, gives information that both have the same biomechanic properties. Peroneus longus should not be used as a first option in ACL reconstruction, but may be used as an alternative donor in cases involving multiple instability that require more tendon donors in the reconstruction. Highlights: No significant difference between peroneus longus and hamstring tendons tensile strength. The tensile strength of the peroneus longus tendon, which is similar to that of hamstring. Peroneus longus should not be used as a first option in ACL reconstruction.